If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10m + 5 = 12m + -28 Reorder the terms: 5 + 10m = 12m + -28 Reorder the terms: 5 + 10m = -28 + 12m Solving 5 + 10m = -28 + 12m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12m' to each side of the equation. 5 + 10m + -12m = -28 + 12m + -12m Combine like terms: 10m + -12m = -2m 5 + -2m = -28 + 12m + -12m Combine like terms: 12m + -12m = 0 5 + -2m = -28 + 0 5 + -2m = -28 Add '-5' to each side of the equation. 5 + -5 + -2m = -28 + -5 Combine like terms: 5 + -5 = 0 0 + -2m = -28 + -5 -2m = -28 + -5 Combine like terms: -28 + -5 = -33 -2m = -33 Divide each side by '-2'. m = 16.5 Simplifying m = 16.5
| b/5.4=-3 | | -23(-2)=x | | 5x+4(x-13)=5(x-8) | | V(2v-1)=0 | | 4y(2y-3x)-2x(x-3y)= | | (-9)[3+3]-12= | | 8n+16.2=1.825 | | 22.5+7.5= | | 3/2(x-5)=/6 | | x(3x-5)=(3x+6)(x-3) | | 6(x-8)=12(x+4) | | 3n+5n+2+n= | | (4q+9)(4q+9)=0 | | 4(x+3)=2x+10+2x | | 46/63-5/7 | | 57+57+123+x=360 | | 5+3(y-4)=5(y+3)-y | | -9+6-12= | | 5+7g=54 | | 12x+17x-6+5=-5x+5-6 | | 63=9(2-w) | | 6-4(5p+9)+3(2+p)=-18 | | 3t-18=4(-3-3/4) | | -6x+5(1)=1 | | 6n=64 | | 4.6x-14.6=5.4 | | 2(n+n+1)=(n+2)-36 | | 3/5x-2=1/5 | | 10y(y+2)+3x=5(3-x) | | 4y-2(x-y)= | | 5x-3x+16=-x+8 | | 9w-8=64 |